ANALISIS PENGARUH RASIO KEUANGAN TERHADAP HARGA SAHAM PADA PERUSAHAAN OTOMOTIF YANG TERCATAT DI BURSA EFEK INDONESIA (BEI) PERIODE 2012-2014 - Nur Hastuti; Aftoni Sutanto (Jurnal Fokus Manajemen Bisnis, 2017)
This research aims to test the influence C (Current  Ratio), IT (Inventory Turnover), DER (Debt Equity Ratio), ROI (Return On Investment), and ROE (Return On Equity) to the stock price on the automotive industry which is listed on the Stock Exchange Indonesia in 2012-2014. The sample in this study is the automotive company. The sampling technique in this study using purposive sampling technique, obtained 12 samples of automotive companies. The test using statistical test multiple linear regression analysis. Partially, the statistical test used was the t test, simultaneously with the F test and the coefficient of determination (R2).  Based  on  the  results  of  this  study  concluded  that  the  partial  CR  (Current Ratio),  IT  (Inventory  Turnover),  DER  (Debt  Equity  Ratio),  ROI  (Return  On Investment), and ROE (Return On Equity) does not affect the value of automotive companies, and simultaneous  no effect on the stock price at the automotive company  2012-2014. R-Squared value (R2) of 0.200 (20.0%) means that the independent variables  affect  the dependent variable of 20.0% and 80.0% side explained by other variables outside the model.